The effect of education on the characteristics of personal socialization in a transitional society - Chikaeva, Karina S.; Abutalipov, Artur R.; Davydova, Galina I.; Vakula, Ivan M.; Shkuropy, Olga I.; Kudinova, Margarita V. (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
In modern sociological science, the topic of social transition at the level of society and the individual is of great interest in the context of the influence of this process on the socialization of the individual. In this regard, researchers are conducting numerous studies on the definition of the structure of socialization of the individual and the stages of this process. Researchers are also interested in the process of personality resocialization, depending on the various states of social mobility of society and the impact of such a factor as the adaptation to life at different stages of socialization (especially in the age of educatio) and during resocialization. It is concluded that the success of the process of resocialization of an individual depends not only on his desire to adapt as fully as possible to change social or other circumstances.